LGBT Inclusion in the gender and development program of the City of Manila, Philippines - Abelgas, Franz Jude S.
As an alternative development policy, Gender and Development (GAD) intends to include marginalized sectors as the centerstage in policy crafting and implementation. With women as the usual face of GAD efforts, it is also relevant to place the Lesbian, Gays, Bisexual, and Transgender (LGBT) community in the concept. As such, this study aims to determine the position of LGBT people in the GAD policy of the City of Manila, Philippines. Using an exploratory case study method, the researcher had employed three phases for data gathering--policy analysis of GAD reports, Key Informant Interviews, and Focus Group Discussions. Findings reveal that the City of Manila utilizes GAD for LGBTs and through institutionalization of gender protection ordinances (i.e., Manila LGBTQI Protection Ordinance of 2020) alongside advocacy building, LGBT protection, and healthcare programs, projects, and activities (PPAs) for both women and LGBTs. An all-gender inclusive approach may be the starting point of reconceptualization to ensure the welfare of the LGBT community through a focus in trans health, same sex marriage/unions, and protection through legislations and ordinances in the city. It is recommended to map the future of Manila GAD to ensure that development and efforts for the LGBTs are intersectional, grassroots based, and driven by social justice. --Provided by the author